Strengthen Integrity Academic Students in the Era of Artificial Intelligence (AI) through Approach Psychology Education Islam - Hilma Dani Situmorang; Mhd Lailan Arqam (Proceeding of The International Conference on Religious Education and Cross - Cultural Understanding, 2025)
Education is the main foundation in the formation of character and quality of human resources throughout the world. However, the development of technology, especially artificial intelligence (AI), has presented new challenges in the world of education, especially in maintaining the academic integrity of students. The convenience offered by AI is often used unethically, such as in plagiarism or manipulation of academic assignments. This phenomenon encourages the importance of an alternative approach that does not only rely on policy and supervision, but also instills strong moral values. This study examines the relevance of the Islamic educational psychology approach in strengthening the academic integrity of students in the AI era. This approach offers solutions based on Islamic values such as muraqabah (awareness of Allah's supervision), muhasabah (self-evaluation), and the habituation of noble morals. The study was conducted using a library research method by analyzing literature related to academic integrity, AI technology, and Islamic educational psychology, including the thoughts of Imam Al-Ghazali. The results of the study show that the Islamic values taught by Al-Ghazali are very relevant in overcoming the challenges of academic integrity caused by the development of AI technology. The principle of muraqabah helps students understand the ethical implications of their academic actions, while muhasabah encourages self-reflection to improve behavior. In addition, the habituation of values such as honesty and responsibility provides a long-term solution in shaping students' characters. This conclusion emphasizes the importance of integrating Islamic values into the higher education curriculum to create an academic environment with integrity and ethics amidst the advancement of modern technology.